An evaluation of intra-hospital transport outcomes from tertiary neonatal intensive care unit. (17th June 2016) - Bastug, Osman; Gunes, Tamer; Korkmaz, Levent; Elmali, Ferhan; Kucuk, Fatma; Adnan Ozturk, Mehmet; Kurtoglu, Selim
Abstract: Introduction : Patient transport has more important side effects in patients in the newborn age group than in other age groups. This study was performed to evaluate the intra-hospital transport of infants in the neonatal intensive care unit(NICU). Methods : A total of 284 babies hospitalized in the neonatal unit and transported inside the hospital were divided into three groups based on their weights at the time of transport. Their places of transport and important changes in the vital functions of the newborn that might have been caused by transport were recorded with a view to understand the vital effects of intra-hospital transport on the newborn. Results : In our unit, the primary reasons for transport were determined to be echocardiography and radiology (26.4% and 25.7%, respectively). In our study, hyperglycemia and hypothermia were among the statistically most significant side effects associated with transport ( p  < 0.05). It was found that 19% and 27% of the patients had hyperglycemia and hypothermia, respectively. There was a significant difference in the blood sugar levels and the body temperature between pre- and post-transport ( p < 0.05). There were no significant differences in the pH, blood gas CO2, heart rate and breath rate values between pre- and post-transport ( p  > 0.05). As expected, the complication rate was higher in babies with low weight. Conclusions : Current weight is useful for assessing the risks of untoward outcomes associated with intra-hospital transport. Protecting patients from hypothermia during the time spent outside of the NICU would reduce the risk of complications.